Performance of Two Extracts Derived from Propolis on Mature Biofilm Produced by Candida albicans - Isabella Letícia Esteves Barros; Flávia Franco Veiga; Lidiane Vizioli de Castro-Hoshino; Monique Souza; Amanda Milene Malacrida; Beatriz Vesco Diniz; Rafaela Said dos Santos; Marcos Luciano Bruschi; Mauro Luciano Baesso; Melyssa Negri; Terezinha Inez Estivalet Svidzinski (MDPI AG, 2022)
Species of the Candida genus represent the third most common cause of onychomycosis, the most frequent and difficult to treat nail infection. Onychomycosis has been attributed to fungi organized in biofilm and some natural products have proved promising for its treatment. This study aimed to evaluate the antibiofilm activity of propolis extract (PE) and its by-product (WPE) on 7-day preformed biofilms produced by Candida albicans in polystyrene microplates, as well as in an ex vivo model on human nail fragments. The cytotoxicity and permeation capacity were also assessed. Firstly, multiple parameters were evaluated over 7 days to elucidate the dynamics of biofilm formation by C. albicans. The cell viability and total biomass did not vary much from the beginning; however, days 3 and 4 were crucial in terms of metabolic activity, which was significantly increased, and the levels of extracellular matrix components, wherein proteins and nucleic acids experienced an increase, but polysaccharide levels dropped. Architecturally, one-day biofilm showed a monolayer of organized cells (blastoconidia, hyphae, and pseudohyphae), while in the seven-day biofilm there was a three-dimensional well-structured and complex biofilm. This yeast was also able to form a biofilm on both surfaces of the nail, without an additional nutritional source. Both extracts showed excellent antibiofilm activity against the 7-day preformed biofilm and were not toxic to Vero cells at concentrations compatible with the antifungal and antibiofilm activities. Both extracts permeated the experimentally infected nail, with WPE being more efficient. The results of this study, taken together, reinforce the potential of these natural products, containing propolis, as a safe option for the topical treatment of onychomycosis.